Perancangan Standard Operating Procedure (SOP) Proses Pembelian Bahan Baku, Proses Produksi dan Pengemasan pada Industri Jasa Boga - Rusda Irawati; Enstien Basuki Woro Hardiastuti (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
The purposes of this research were to design a Standard Operating Procedure (SOP) for the purchase of raw materials, production processes, and packaging of products in PT. KSM Catering & Bakery Batam. Data collected use documentation and interview method to collect information. The data analysis done by using the Miles & Huberman method. Results from this research that the draft Standard Operating Procedure (SOP) for the purchase of raw materials, production processes menu and packaging products.